Proses Pemesinan Pada Produksi Mesin Pencacah Kompos PPO-100E Pada PT. XYZ - Mu’min Muhaemin,; Nanang Hidayat,; H. Jojo Sumarjo,; Ing. Reza Setiawan,; Deri Teguh Santoso, (Journal Serambi Engineering, 2024)
The development of the world of technology and industry has greatly influenced various sectors, including the manufacturing industry. Research to design a small-scale composting tool that can be directly processed and used. The composting process can help reduce organic waste and produce compost that is useful for agriculture or other purposes. Composting machine design using Autodesk Inventor software can be a good step to produce an accurate and implementable 3D model. The material used in the shredding machine for compost storage is stainless steel which has anti-corrosion properties or is resistant to rust and contains 10.5% chromium metal, which gives the material rust-resistant properties. The engine drive on the compost chopping machine uses a dynamo to provide ease of use. Each shelf/drawer has a chopping space volume of 0.19602 m3 and the chopping process per hour can reach 101 kg/hour with a rotation of 1058 rpm.